Brazilian Artisanal Cheeses: An Overview of their Characteristics, Main Types and Regulatory Aspects. Issue 5 (21st August 2019) - Kamimura, Bruna A.; Magnani, Marciane; Luciano, Winnie A.; Campagnollo, Fernanda B.; Pimentel, Tatiana C.; Alvarenga, Verônica O.; Pelegrino, Beatriz O.; Cruz, Adriano G.; Sant'Ana, Anderson S.
Abstract: A large variety of cheeses exist in Brazil, reflecting historical and cultural aspects. Brazilian artisanal cheeses present differences in the processing, ripening time (when applied), type of milk used, texture, size, shape, color, moisture content, flavor, the use or not of starter cultures, among others. This review describes the main artisanal cheeses produced in Brazil, focusing on general and particular characteristics associated with their making process and geographical identity. Overall, the high variability of the physicochemical data and deficiency of information on sensorial properties of Brazilian artisanal cheeses were noticed. On the other hand, culture‐dependent methods were mostly used to expand the knowledge into the microbiology of these cheeses, whereas their microbial diversity has been recently discovered through the use of 16S rRNA gene sequencing‐based methods. The certification of a geographical indication for Brazilian artisanal cheeses may encompass an essential milestone for adding value to these products. Regardless of their significance in the diet, culture, and economy of producing regions, taken together, the reviewed literature discloses the need of insightful studies to generate scientific data to support the expansion of the market, while ensuring the protection of historic aspects related to the production of Brazilian artisanal cheeses.